A perturbation bound on a class of dynamical model updating problem and a method of keeping its sparse structure. (March 2016) - Xie, Dongxiu; Huang, Ningjun; Wang, Aiwen
Abstract: It establishes a perturbation bound of a generalized centrosymmetric model updating problem with spectra constraints. A method is presented to preserve the sparsity of the model. The numerical examples show that the method is feasible and effective. Abstract : Highlights: Numerical theory and method in Mechanical, Aeronautical and Civil Engineering. A new perturbation bound of some constraints model updating problem. A method is presented to preserve the sparsity of the model. The numerical examples show that the method is feasible and effective.